Waldenstrom Macroglobulinemia and the Eye: A case report and review - Bhavsar, Mayur; Cercone, Joseph; Chiu, Catherine (Canadian Journal of Optometry, 2021)
Waldenstrom macroglobulinemia (WM) is a rare, malignant lymphoproliferative B-cell disorder causing an excessive buildup of monoclonal protein. WM is associated with excessive buildup of IgM, which can cause blood hyperviscosity and damage many organ systems. This case report describes a patient who was followed annually but rapidly developed posterior pole and significant midperipheral hemorrhages secondary to a hyperviscosity condition of the retina. Management of this condition is dependent on macular involvement and must be co-managed with an oncologist.